Giant sliding inguinal hernia requiring intraoperative aspiration of fluid: a case report and literature review. Issue 8 (26th August 2021) - Davis, Tyler; Vivens, Mica; Barghuthi, Lutfi; Ismael, Hishaam
Abstract: Giant inguinal hernias are defined as inguinal hernias that extend below the midpoint of the inner thigh when the patient is in the standing position or an anteroposterior diameter of at least 30 cm or a laterolateral diameter of 50 cm with non-reducibility for >10 years. This article presents a 39-year-old male with a five-year history of a giant left inguinal hernia that was treated with left inguinal hernia repair with mesh, orchiectomy, complicated scrotoplasty, intraoperative ultrasound and aspiration of 3.9 L of fluid from the hernia sac. Surgical repair of giant inguinal hernias can be challenging and is associated with a variety of complications. Various modalities have been described to assist in hernia reduction including debulking, or, as in this case, aspiration of the hernia sac and a preperitoneal incision. Although the Lichtenstein tension free repair is commonly used, no standard approach has been accepted.